Distinctive Asymmetrical Decentralization in the Archipelagic Region: The Case of West Nusa Tenggara Province of Indonesia - Restu Karlina Rahayu (Jurnal Transformative)
Decentralization has repercussions for the area in a variety of areas, including political, social, cultural, financial, defense and security, and public services, among others. Sumbawa Island and Lombok Island are the two principal islands that make up West Nusa Tenggara. There are 280 islands in all, 32 of which are inhabited. Sumbawa Island is one-third the size of Lombok Island in terms of area, but Lombok Island has a population that is about three times that of Sumbawa Island. This study contends that because the archipelagic region is not organized by its island-specific traits but rather around land-based development, this has the potential to exacerbate discrepancies between islands. This study found that, there are only minimal maritime authorities in the archipelagic province in managing archipelagic water, and there is fiscal and ethnic disparity between the Lombok and Sumbawa Islands. Moreover, there are inequalities in health care facilities and medical staff between Lombok and Sumbawa Island, the small population of Sumbawa Island has an impact on educational resources, and the maritime infrastructure on the other small islands surrounding Sumbawa Island is inadequate.